Implementasi Pemberian Jus Belimbing Untuk Menurunkan Tekanan Darah Pada Keluarga Penderita Hipertensi Di Wilayah Kerja Puskesmas Kartini Kota Pematang Siantar - Felisia Br. Sitepu; Derma Wani Damanik (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Introduction: Hypertension refers to a persistent increase in pressure in the arteries, with a systolic pressure of ≥ 130 mmHg and a diastolic pressure of ≥ 80 mmHg. This condition is a blood vessel disorder that restricts the flow of oxygen and nutrients to the body's tissues that need them. The WHO reports that 1.28 billion adults aged 30-79 worldwide suffer from hypertension, the majority of whom live in low- and middle-income countries. Hypertension is a leading cause of premature death worldwide. One method used to treat hypertension is by administering starfruit juice. Objective : The aim of this study was to implement of starfruit juice giving to lower blood pressure in families with hypertension. Method: The design of this study used quantitative research through a case study method approach. The number of research samples was 2 families aged 39-49 years in the family, where this research was conducted in the Kartini Pematang Siantar Health Center Work Area. Results: The results of the implementation of starfruit juice administration which was carried out for 3 days with a duration of 10-30 minutes. In family I, it shows the level of family knowledge related to the provision of starfruit juice with results before the action of 159/90mmHg and after the action the family experienced a decrease in blood pressure to 130/80mmHg and in family II, it shows the level of family knowledge related to the provision of starfruit juice with results before the action of 150/90mmHg and after the action the family experienced a decrease in blood pressure to 130/80mmHg Conclusion: Therapy of giving starfruit juice to hypertensive patients is effective in lowering blood pressure. Conclusion: It is expected that the client's family if the family experiences hypertension can implement the implementation of giving starfruit juice gradually so that the expected results are achieved by lowering blood pressure in the family.